1983
DOI: 10.1177/030089168306900211
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chest X-Ray in the Follow-Up of Primary Breast Cancer

Abstract: The results of chest X-ray (CXR) survey in the follow-up of 1697 breast cancer patients are reviewed. Intrathoracic metastases (ITM) accounted for 26% of total first recurrences, but the rate dropped to 13% if isolated ITM and to 7% if asymptomatic isolated ITM were considered. Thus the role of CXR survey was limited to the detection of 39 cases of isolated ITM in the asympatomatic phase out of 7100 patients-year for a total number of 11,543 CXR examinations. Moreover, no difference in mean survival was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…The high accuracy of the tumour marker panel in our study, particularly diagnostic sensitivity in the detection of distant metastases, may partly be due to the high frequency of test repetition compared to that of CXR and LE. However previous studies evaluating the accuracy of intensive follow-up with instrumental examinations for the same purpose including CXR and/or LE did not show accuracy values comparable to those obtained by the tumour marker panel we used (Ciatto and Herd-Smith, 1983;Logager et al, 1990;Schapira and Urban, 1991;The GIVIO Investigators, 1994). The accuracy and negative predictive value of the CEA-TPA-CA15.3 tumour marker panel which we previously reported for diagnosis of bone metastases in patients with equivocal BS (Nicolini et al, 1999) were similar to those we found in this study for diagnosis of chest or liver metastases in patients with equivocal CXR or equivocal LE.…”
Section: Discussionmentioning
confidence: 73%
“…The high accuracy of the tumour marker panel in our study, particularly diagnostic sensitivity in the detection of distant metastases, may partly be due to the high frequency of test repetition compared to that of CXR and LE. However previous studies evaluating the accuracy of intensive follow-up with instrumental examinations for the same purpose including CXR and/or LE did not show accuracy values comparable to those obtained by the tumour marker panel we used (Ciatto and Herd-Smith, 1983;Logager et al, 1990;Schapira and Urban, 1991;The GIVIO Investigators, 1994). The accuracy and negative predictive value of the CEA-TPA-CA15.3 tumour marker panel which we previously reported for diagnosis of bone metastases in patients with equivocal BS (Nicolini et al, 1999) were similar to those we found in this study for diagnosis of chest or liver metastases in patients with equivocal CXR or equivocal LE.…”
Section: Discussionmentioning
confidence: 73%
“…Of 523 relapses, only 39 were identified solely by chest x-ray. 50 Radionucleide bone scans also have not been found to be of value in asymptomatic patients with normal serum chemistry values. 51 Two randomized, controlled studies indicate that bone scans are of no utility in asymptomatic patients regardless of serum chemistry values.…”
Section: Breast Cancermentioning
confidence: 99%
“…Its actual impact on altering the survival rate, by the early detection of recurrences, is not yet clear. Presently, it appears that the median survival is similar in both symptomatic and asymptomatic patients having pulmonary metastases [3].…”
Section: Contralateral Breastmentioning
confidence: 84%